S100 and CD34 positive spindle cell tumor with prominent perivascular hyalinization and a novel NCOA4-RET fusion - Michal, Michael; Ptáková, Nikola; Martínek, Petr; Gatalica, Zoran; Kazakov, Dmitry V; Michalová, Květoslava; Stoláriková, Lýdia; Švajdler, Marián; Michal, Michal (Genes, chromosomes & cancer, 2019)
We report a case of a 35-year old male patient with a tumor located in the deep dermis on his forearm. The lesion was completely excised but recurred 4 years later. The patient showed no signs of neurofibromatosis type 1. The morphology and immunophenotype of the tumor corresponded to the recently characterized group of soft tissue spindle cell lesions defined by a relatively uniform cytomorphology, patternless architecture, conspicuous stromal and perivascular hyalinization, S100 and CD34 coexpression and recurrent fusions involving RAF1, BRAF, and NTRK1/2 genes. Using a 592-gene panel and massively parallel next-generation sequencing platform, we initially detected only NF1 gene mutation in our case. However, further molecular testing with Archer fusion assay revealed a novel NCOA4-RET gene fusion, adding it to the list of multiple kinase fusions originally reported in these tumors. Although break-apart FISH showed false negative result due to the presence of intrachromosomal rearrangement, RT-PCR confirmed the fusion transcript. Knowing the exact fusion is of great clinical importance especially for patients within the aggressive subset of these neoplasms that could be treated with selective kinase inhibitors. The presented case underscores the benefits of massively parallel sequencing as the types and number of gene fusions these tumors can potentially harbor render single-gene assays such as FISH impractical, and in this particular case, also insensitive.
Keywords: kinase fusions; Hyalin; Nuclear Receptor Coactivators; Male; antigeny CD34; mutace; onkogenní fúze; soft tissues; škára; koaktivátory jaderných receptorů; Proto-Oncogene Proteins c-ret; Soft Tissue Neoplasms; proteiny S100; Adult; dospělí; mužské pohlaví; S100 and CD34 positive spindle cell tumor; Antigens, CD34; Dermis; NF1 gene mutation; Neurofibromin 1; S100 Proteins; NCOA4-RET; lidé; hyalin; protoonkogenní proteiny c-ret; neurofibromin 1; Humans; nádory měkkých tkání; Mutation; infantile fibrosarcoma; Oncogene Fusion